MICA-129 Dimorphism and Soluble MICA Are Associated With the Progression of Multiple Myeloma - Zingoni, Alessandra; Vulpis, Elisabetta; Cecere, Francesca; Amendola, Maria G.; Fuerst, Daniel; Saribekyan, Taron; Achour, Adnane; Sandalova, Tatyana; Nardone, Ilaria; Peri, Agnese; Soriani, Alessandra; Fionda, Cinzia; et al. (Frontiers in Immunology, 2018)
NK cell are immune innate effectors playing a pivotal role in the immunosurveillance of multiple myeloma (MM) since they are able to directly recognize and kill MM cells. In this regard, among activating receptors expressed by NK cells, NKG2D represents an important receptor for the recognition of MM cells, being its ligands expressed by tumor cells and being able to trigger NK cell cytotoxicity. The MHC class I-related molecule A (MICA) is one of the NKG2D ligands; it is encoded by highly polymorphic genes and exists as membrane-bound and soluble isoforms. Soluble MICA (sMICA) is over-expressed in the serum of MM patients and its levels correlate with tumor progression. Interestingly, a methionine (Met) to valine (Val) substitution at position 129 of the α2 heavy chain domain classified the MICA alleles into strong (MICA-129Met) and weak (MICA-129Val) binders to NKG2D receptor. We addressed whether the genetic polymorphisms in the MICA-129 alleles could affect MICA release during MM progression. The frequencies of Val/Val, Val/Met and Met/Met MICA-129 genotypes in a cohort of 137 MM patients were 35%, 43% and 22%, respectively. Interestingly, patients characterized by a Val/Val genotype exhibited the highest levels of sMICA in the sera. In addition, analysis of the frequencies of MICA-129 genotypes among different MM disease states revealed that Val/Val patients had a significant higher frequence of relapse. Interestingly, NKG2D was downmodulated in NK cells derived from MICA-129Met/Met MM patients. Results obtained by structural modelling analysis suggested that the methionine to valine dimorphism could affect the capacity of MICA to form an optimal template for NKG2D recognition. In conclusion, our findings indicate that the MICA-129Val/Val variant is associated with significantly higher levels of sMICA and the progression of MM, strongly suggesting that the usage of soluble MICA as prognostic marker has to be definitely combined with the patient MICA genotype.